Counselling Research in a Different Key: The Promise of Human Science Perspective - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2011)
It is maintained in this article that the human science perspective holds great promise with regard to achieving methodological balance in counselling research. In the interests of increasing the likelihood that this promise will be realized, an attempt is made: 1) to provide the reader with a perspective on the meaning, structure, and content of the human science orientation; (2) to identify and illuminate selected qualities of "being" and of "mind" that appear to be related to human science research competence; and (3) to suggest some possibilities for the deliberate facilitation of such competence. The article concludes with the raising of selected issues which will need to be dealt with if progress in the direction of achieving a high degree of fidelity to human experience in counselling research is to continue to be made.